When governments break the law : the rule of law and the prosecution of the Bush administration - Sarat, Austin; Hussain, Nasser, 1965- (New York : New York University Press, 2016)
Recent controversies surrounding the War on Terrorism and the US interventions in Iraq and Afghanistan have brought rhetoric about the rule of law to fever pitch, and no issue is more live than the issue of possible prosecution of officials of the Bush administration.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: War on Terrorism, 2001-2009.; Rule of law; Administrative responsibility; International crimes; Terrorism -- Prevention -- Law and legislation -- United States; United States -- Politics and government -- 2001-2009.; Law; United States of America, USA; Political control & freedoms; Jurisprudence & general issues; Law & society, sociology of law; Government powers